Clinical prediction of 5-year survival in systemic sclerosis: validation of a simple prognostic model in EUSTAR centres. Issue 10 (21st July 2011) - Fransen, J; Popa-Diaconu, D; Hesselstrand, R; Carreira, P; Valentini, G; Beretta, L; Airo, P; Inanc, M; Ullman, S; Balbir-Gurman, A; Sierakowski, S; Allanore, Y; et al.
Abstract : Objective: Systemic sclerosis (SSc) is associated with a significant reduction in life expectancy. A simple prognostic model to predict 5-year survival in SSc was developed in 1999 in 280 patients, but it has not been validated in other patients. The predictions of a prognostic model are usually less accurate in other patients, especially from other centres or countries. A study was undertaken to validate the prognostic model to predict 5-year survival in SSc in other centres throughout Europe. Methods: A European multicentre cohort of patients with SSc diagnosed before 2002 was established. Patients with SSc according to the preliminary American College of Rheumatology classification criteria were eligible for the study when they were followed for at least 5 years or shorter if they died. The primary outcome was 5-year survival after diagnosis of SSc. The predefined prognostic model uses the following baseline variables: age, gender, presence of urine protein, erythrocyte sedimentation rate (ESR) and carbon monoxide diffusing capacity (DLCO). Results: Data were available for 1049 patients, 119 (11%) of whom died within 5 years after diagnosis. Of the patients, 85% were female, the mean (SD) age at diagnosis was 50 (14) years and 30% were classified as having diffuse cutaneous SSc. The prognostic model with age (OR 1.03), male gender (OR 1.93), urine protein (OR 2.29), elevated ESR (1.89) and low DLCO (OR 1.94) had an area under the receiver operating characteristic curve of 0.78. Death occurred in 12 (2.2%) of 509 patients with no risk factors, 45 (13%) of 349 patients with one risk factor, 55 (33%) of 168 patients with two risk factors and 7 (30%) of 23 patients with three risk factors. Conclusion: A simple prognostic model using three disease factors to predict 5-year survival at diagnosis in SSc showed reasonable performance upon validation in a European multicentre study.